Ubiquitin Phosphorylation at Thr12 Modulates the DNA Damage Response - Walser, Franziska; Mulder, Monique P C; Bragantini, Benoît; Burger, Sibylle; Gubser, Tatiana; Gatti, Marco; Botuyan, Maria Victoria; Villa, Alessandra; Altmeyer, Matthias; Neri, Dario; Ovaa, Huib; Mer, Georges; et al. (Molecular cell, 2020)
The ubiquitin system regulates the DNA damage response (DDR) by modifying histone H2A at Lys15 (H2AK15ub) and triggering downstream signaling events. Here, we find that phosphorylation of ubiquitin at Thr12 (pUbT12) controls the DDR by inhibiting the function of 53BP1, a key factor for DNA double-strand break repair by non-homologous end joining (NHEJ). Detectable as a chromatin modification on H2AK15ub, pUbT12 accumulates in nuclear foci and is increased upon DNA damage. Mutating Thr12 prevents the removal of ubiquitin from H2AK15ub by USP51 deubiquitinating enzyme, leading to a pronounced accumulation of ubiquitinated chromatin. Chromatin modified by pUbT12 is inaccessible to 53BP1 but permissive to the homologous recombination (HR) proteins RNF169, RAD51, and the BRCA1/BARD1 complex. Phosphorylation of ubiquitin at Thr12 in the chromatin context is a new histone mark, H2AK15pUbT12, that regulates the DDR by hampering the activity of 53BP1 at damaged chromosomes.